A RADAR-Based Assay to Isolate Covalent DNA Complexes in Bacteria - Katie J. Aldred; Adeline Payne; Olivia Voegerl (MDPI AG, 2019)
Quinolone antibacterials target the type II topoisomerases gyrase and topoisomerase IV and kill bacterial cells by converting these essential enzymes into cellular poisons. Although much is known regarding the interactions between these drugs and enzymes in purified systems, much less is known regarding their interactions in the cellular context due to the lack of a widely accessible assay that does not require expensive, specialized equipment. Thus, we developed an assay, based on the “rapid approach to DNA adduct recovery,„ or RADAR, assay that is used with cultured human cells, to measure cleavage complex levels induced by treating bacterial cultures with the quinolone ciprofloxacin. Many chemical and mechanical lysis conditions and DNA precipitation conditions were tested, and the method involving sonication in denaturing conditions followed by precipitation of DNA via addition of a half volume of ethanol provided the most consistent results. This assay can be used to complement results obtained with purified enzymes to expand our understanding of quinolone mechanism of action and to test the activity of newly developed topoisomerase-targeted compounds. In addition, the bacterial RADAR assay can be used in other contexts, as any proteins covalently complexed to DNA should be trapped on and isolated with the DNA, allowing them to then be quantified.